Влияние угла места цели на точность стрельбы из вооружения объектов БТТ - Мошнин, В. Н.; Мирошниченко, Ю. В.; Царев, И. В. (НТУ "ХПИ", 2006)
The analysis conducted in the article focuses on the angle of sight influence on tank gun and BMP-2 2A42 gun fire accuracy. The article also contains recommendations in practical influence calculation.
Keywords: бронетанковая техника; точность стрельбы; угол прицеливания; танковая пушка